Handbook of research on health systems and organizations for an aging society - Fonseca, César, 1973-; Lopes, Manuel José; Mendes, David, 1966-; Mendes, Felismina R. P.; Garcia-Alonso, José (Medical Information Science Reference, 2020)
"This book explores the development and management of health systems and organizations in relation to individuals aged 65 and over"--Provided by publisher.